Arthashastra as a Pedagogical Resource: Cultivating Peace Values through Ancient Statecraft - Smaranika Samal; DR. Dipanshu Sharma; Ishita Mishra (Recent Trends in Social Studies, 2026)
One of the earliest Indian texts on statecraft, including the governance of a state, its economics, diplomacy, military strategy and ethics, is the Arthashastra attributed to Kautilya (Chanakaya), which was written around the 4th century BCE. Although commonly viewed through the prism of realism and the power and pragmatism, peace (shanti) is a strategic and ethical value of the text that ensures stability, prosperity (artha) and welfare (yogakshema) to the society. Kautilya advocates for diplomacy, alliances, and negotiation over war in most cases, as a perpetual struggle would be detrimental to the state's foundation. This paper explores the Arthashastra as a pedagogical guide to instil peace values in contemporary learning. It determines the implicit concepts of peace, including the preference of sandhi (peace/treaty-making) in the context of sadgunya, ethical governance based on dharma, welfare policies in times of crisis, and a culturally contextualised concept of harmony, in opposition to Western concepts. These aspects provide a realistic approach of pragmatism that instructs on critical thought, ethical choice, and non-violent strategy. The paper suggests the curriculum integration in international relations, ethics, and conflict resolution through excerpts, role-playing diplomatic situations, learning cases, and comparisons with Machiavelli. It highlights the benefits of promoting duty, justice, compassion, global citizenship, and cultural awareness, as well as addressing issues such as the misperception of power-centred elements, anachronistic threats, and ethical dilemmas in navigating the realism-idealism spectrum.
Keywords: Arthashastra; Kautilya; ancient Indian wisdom; ethical governance; indigenous pedagogy; peace education; statecraft; strategic diplomacy